Хорго вулканы үүсэл, хэлбэрийн онцлог - Э.Алтанболд; Х.Уламбадрах (Geological Issues, 2023)
The book, Cenozoic alkaline basalts of Mongolia and their deep inclusion, volcano existing during Cenozoic was firstly written by V.V.Kepejenskas in 1979 was the first comprehensive monograph including integration of results in many years. The aim of my paper is to define volcanic origin of the Khorgo as the one representative and its morphology or landscape based on such monograph. In Mongolia, there is nothing about study on morphological features by volcanic activity. There are much morphology formed due to effusive effect of lava with basic content in which it’s very crucial to find out which type of morphology had been distributed and relation between origin preferring Khorgo volcanic issues. Thickness of crust of Tariat volcano was 45 km during its activity (Stoch, Kopylova 1995; Ionov 2002). Harris (2009) Due to the ground hot spot, continent became thinner resulted as Khangai magmatic activity. Many intermissive breakdowns through earth crust were formed here. Therefore, due to such formation of intermissive breakdown or one of the main breakdown extending from north-west to south east became stream for basic lava resulted in formation of Khorgo volcano. Lava stream consisting of silicon oxide less than 45% and predominant kali content with fluidity formed as barrier blocking the Suman river valley which led to the formation of Terkhiin Tsagaan lake. Research showed that it was lava elevation among morphologies formed by lava with basic content. The steepness of crater of Khorgo volcano is around 45 degrees while its depth and diameters are 100 m and 500 m respectively. Scientists have predicted that the age. Khorgo volcano as approximately 1.8-2.0 million years in quaternary. Therefore, it’s needed to precise the age of its rocks.